2008
DOI: 10.1074/jbc.m704531200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Heparin Saccharides Promote FGF2 Mitogenesis through Two Distinct Mechanisms

Abstract: Heparin-like saccharides play an essential role in binding to both fibroblast growth factors (FGF) and their receptors at the cell surface. In this study we prepared a series of heparin oligosaccharides according to their size and sulfation level. We then investigated their affinity for FGF2 and their ability to support FGF2 mitogenesis of heparan sulfate-deficient cells expressing FGFR1c. Tetra-and hexasaccharides bound FGF2, but failed to dimerize the growth factor. Nevertheless, these saccharides promoted F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 36 publications
(44 reference statements)
6
79
0
Order By: Relevance
“…The authors describe a 2:2:1 complex that is not limited to the NRE of HS chains. Evidence exists for both the Schlessinger and Pellegrini complexes (40,41), and it has recently been proposed that both complexes may be physiologically relevant, depending on the HS structures present (42).…”
Section: Discussionmentioning
confidence: 99%
“…The authors describe a 2:2:1 complex that is not limited to the NRE of HS chains. Evidence exists for both the Schlessinger and Pellegrini complexes (40,41), and it has recently been proposed that both complexes may be physiologically relevant, depending on the HS structures present (42).…”
Section: Discussionmentioning
confidence: 99%
“…A major mechanistic theory of heparin's activity in FGF signaling is its ability to stabilize the ternary complex of dimerized FGF-FGFR pairs (4). In addition, recent studies suggest that heparin may increase FGF signaling through mechanisms in addition to receptor complex stabilization (24). Cell-surface heparan sulfates are also effective in facilitating FGF-2 signaling and can stabilize the ternary FGF-signaling complex (4).…”
Section: Discussionmentioning
confidence: 99%
“…In another scenario, HS first induces oligomerization of FGF molecules and subsequently enables FGFR dimerization, as proposed in the 2:2:1 FGF1⅐FGFR2c⅐heparin ternary complex model (9). These two binary FGF⅐FGFR and FGF⅐HS complexes may co-exist as the driving force for ternary signaling complex assembly, which can be regulated by the different length and sulfation patterns of heparin⅐HS saccharides (11). Here we have shown that heparinbound anosmin-1 facilitates FGF2⅐FGFR1 as the preferred fundamental binary complex, resulting in anosmin-1⅐FGF2⅐ FGFR1⅐heparin complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…Two crystal structures have been proposed to demonstrate how the FGF⅐FGFR⅐heparin complex is assembled (9,10). Recent evidence suggests that both may be biologically relevant (11,12).…”
Section: Fgfmentioning
confidence: 99%
See 1 more Smart Citation